Matheme of Phantasy and Object of Desire in “Hamlet” - DIOȘAN, Livia (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
“What is a father?” That is the question. This paper discusses Hamlet emphasizing the concept of desire and its formation for any human being. From a Lacanian psychoanalytical point of view, a difference between need, demand, and desire will be considered, in order to better understand how desire appears from the fabric of a topological surface and takes its place in the reality of the subject. Then the matheme of phantasy and the various objects that present themselves in Hamlet, namely Ophelia and others, as well as the stages of the relationship between Hamlet and his object will be analyzed. The analysis of the obsessional structure allows a better understanding of the movement of desire and action in Hamlet, without stating an obsessional structure in the character itself because what is interesting in the end is that Hamlet actually illustrates the place of desire for any human being. Following Lacan’s seminars, the paper will approach the relationship between faith and death, as well as the Borromean place of the Symbolic, with the consequences that emerge when the Symbolic crashes. This way, one could get closer to the fundamental question, pertaining to the function of the father and the unfortunate lifting of the veil that places Hamlet in an impossible position from which he cannot act to fulfill his destiny because the existence of desire is conditioned by the faith in death. The answer to the question would be that a father is seen in the context of actioning as a function, like a mathematical function, to orient the desire of the mother. Instead, in Hamlet, there is only legacy of a sin.